A)(a +1)²+(a-2)²-2(a-2)² dla a=5,5
b)(ax+1)²-(ax+1)(ax-1)+ax+1 dla a= 1/3 x=√2
c)√2+√3)(√2-√3)-(√5+√7)(√5-√7)
d)(3-2√5)(3+2√5)-2(√5-1)²
e)(3-√2)(3+√2)+2√5(√5-1)-(1-√5)²
f)(√7+2)(√7-2)+2√3(√3-1)-(1-√3)²
g)(√6-√3)²-(√6-1)(√6-√3)+√3(1-√2)
h)(x√3+√2)(2+3x²)(2-x√3)

Proszę o rozwiązanie z góry dziękuje :**

2

Odpowiedzi

2009-10-17T23:32:05+02:00
A) (5,5+1)²+(5,5-2)²-2(5,5-2)²=42,25 + 12,25 - 24,5 = 30
b) 1/3√2+1
c)√5×√-1-√12×√2=√-5 - √-24≡√-29

dalej już nie mam siły robić : |
1 5 1
Najlepsza Odpowiedź!
2009-10-17T23:51:08+02:00
Nie zrobiłam d,g i h (*-znaczy razy)
a). (a+1)^+(a-2)^-2(a-2)^= (a^+2a+1)+(a^-2a+4)-2(a^-2a+4)=(a^+2a+1)+(a^-2a+4)-2a^+4a-8=a^+2a+1+a^-2a+4-2a^+4a-8=1+4+4a-8=-3+4a
-3+4*5,5=-3+22=19
b).(ax+1)^-(ax+1)(ax-1)+ax+1=(a^x^+2ax+1)-(a^x^-1)+ax+1=a^x^+2ax+1-a^x^+1+ax+1=2ax+x+1+ax+1
2*1/3√2+3+1/3√2=2/3√2+1/3√2+3=3+√2
c).(√2+√3)(√2-√3)-(√5+√7)(√5-√7)=((√2)^-(√3)^)-((√5)^-(√7)^)=(2-3)-(5-7)=2-3-5+7=1
e).(3-√2)(3+√2)+2√5(√5-1)-(1-√5)^=(3^-(√2)^)+2√5(√5-1)-(1-2√5+(√5)^)=9-2+2*5-2√5-1+2√5-5=7+10-2√5-1+2√5-5=11
f).(√7+2)(√7-2)+2√3(√3-1)-(1-√3)^=((√2)^-2^+2√3(√3-1)-(1-2√3-(√3)^)=2-4+2*3-2√3-1+2√3-9=2+6-1-9=-2
1 5 1